Reward and Compensation as a Determinant of Employee Commitment: A Survey of Ktda Tea Factories in Kenya - Milgo, Alice Chepkorir; Namusonge, Gregory; Kanali, Christopher; Makokha, Elizabeth Nambuswa (My University, 2014)
The purpose of this study was to investigate the determinants of employee commitment in tea organizations in Kenya. Strong commitment is correlated with high productivity, while low commitment lowers productivity. The primary objective of this research was to determine the influence of reward and compensation on employee commitment in tea factories in Kenya. To achieve this objective a survey was conducted to canvas the opinions of respondents in public KTDA tea factories in Kenya. Purposive sampling was employed to select six (6) factories based on second payment known as bonus; with three (3) high paying and three (3) low paying. Stratified sampling technique was used to categorize population into managers and employees. Random sampling was used to give the sample size of employees. A total of 273 respondents were randomly selected from a population frame of 861 employees. Qualitative and quantitative data was collected by use of selfadministered structured questionnaires and interview schedule. Analysis of data showed low paying factories had a lower average mean in all aspects of reward and compensation 54.93% compared to high paying at average mean 71.60%.Further analysis using Spearman’s rank correlation test revealed significant relationship (P=0.00<0.01) between reward and compensation and commitment. The study confirmed the significance of reward and compensation as a determinant of employee commitment. This study has implications for management of KTDA tea factories in Kenya since they can influence employees to achieve optimized motivation and commitment, by designing a good reward and compensation that is perceived as fair, equitable and consistent.
Keywords: Reward and Compensation; Employees; Commitment; Organization; Enlisted Factories